The Working Alliance Inventory's Measurement Properties: A Systematic Review - Paap, Davy; Karel, Yasmaine H. J. M.; Verhagen, Arianne P.; Dijkstra, Pieter U.; Geertzen, Jan H. B.; Pool, Grieteke (Frontiers in Psychology, 2022)
Measurement properties of the Working Alliance Inventory (WAI) and its various translations and adaptations for specific target groups have been investigated for over 30 years. No systematic review analyzing studies on measurement properties of the WAI has been conducted to date. COnsensus-based Standards for the selection of health Measurements INstruments (COSMIN) were developed for conducting high-quality systematic reviews on measurement properties in a transparent and standardized way. Aim of this study was to systematically review studies on measurement properties of the WAI, and its adapted versions, within psychotherapy, and other healthcare contexts using COSMIN criteria. PsycINFO, Medline, and EMBASE were searched (1989-2021). In all phases of the review procedure, study selection, data extraction, risk of bias assessment, rating of the quality of measurement properties, and rating of the quality of evidence for measurement properties, disagreement between reviewers was resolved by discussion. Results on validity, internal structure, reliability, construct validity, and responsiveness were analyzed. In total 66 studies were included. In most studies, evidence for measurement properties was according to COSMIN criteria, insufficient, lacking, or conflicting. Content validity was rated insufficient because neither patients nor healthcare professionals were involved in the development and validation process. Hence evidence for content validity of the WAI is unknown. Conflicting evidence was found for structural validity. Evidence for internal consistency could not be established. Limited evidence was found for inter-rater reliability and convergent validity. Conflicting evidence was also found for test-retest reliability and divergent validity. COSMIN criteria exposed persistent problems in validation studies of the WAI. These findings may indicate that measurement properties of the WAI are not up to current standards, or that COSMIN criteria may be less appropriate for assessing measurement properties of the WAI, or it could indicate both. The results of this systematic review suggest that WAI outcomes should be interpreted with caution and further research is needed regarding the content validity and hypotheses development. For the future, the theoretical framework underlying the measurement of the working alliance needs to be studied in psychotherapy and other health contexts, and tested in methodologically sound studies.